Early Left Ventricular Thrombus Formation in a COVID-19 Patient with ST-Elevation Myocardial Infarction. (20th July 2020) - Sharma, Harish; George, Sudhakar
Abstract : Background . Left ventricular thrombus (LVT) is a complication of acute myocardial infarction (AMI) due to localised haemostasis. LVT is typically seen 3-12 days following AMI and is seldom seen within the first 24 hours. LVT increases the risk of mortality due to systemic thromboembolism. Patients with Coronavirus Disease-19 (COVID-19) are potentially hypercoagulable and this may promote early development of LVT. Case . A 50-year-old man with no past medical history was admitted with a severe diabetic ketoacidosis following a 4-day history of cough and fever. The patient tested positive for COVID-19 and required intensive care treatment for ventilation and haemofiltration. After returning to ward-based care, the patient developed chest pain and electrocadiographic changes consistent with an acute anterior ST-elevation myocardial infarction. Emergency percutaneous coronary intervention was performed to the left anterior descending artery. However, the patient developed diuretic-resistant pulmonary oedema and a bedside echocardiogram revealed significant LVT despite only 4 hours of chest pain. The thrombus was associated with the anteroseptal wall of the left ventricle which was hypokinetic but not aneurysmal. An intra-aortic balloon pump (IABP) was inserted, but the patient developed ipsilateral lower limb ischaemia due to the formation of thrombus in the femoral artery and irreversible cardiogenic shock from which he ultimately succumbed. Conclusion . COVID-19-positive patients are potentially hypercoagulable, and MI in this population may precipitate LVT earlier than expected. Consideration should be made for routine early screening of post-MI COVID-19 patients for LVT. If detected, anticoagulation may reduce the risk of cardiovascular mortality in this high-risk group.